A study about the drop out in organized youth sports competition - Turpin, J. A. P.; Llorca, S. (Journal of Human Sport & Exercise, 2007)
The abandonment of the young people in the sport competition is a present subject, that it can take to us to even question the philosophy of the sports scholastic for young people. The present study tries to demonstrate the index of participation of the young people in the sport competition, in relation to the stages established by the different official organisms, together with the set of practiced sports more, as much of collective way as individual, that they include to the scholastic sport. This study is a descriptive analysis of the present reality of the scholastic sport of the city of Alicante, based on the data contributed by the Municipal Patronage of sport, during a school year.